Penguatan Karakter Peserta Didik Melalui Pembelajaran Agama Islam Berbasis Multikultural di SMAN 1 Jombang - Elik Khoirun Nisa (STAIFAS-Press, 2018)
Indonesia has many cultures, customs, tribes, nations and religions. This diversity can lead to conflict, because of incompatibility between individuals with other in accepting the differences. This article discusses the diversity and the role of Islamic religious teachers in implementing multicultural education at SMAN 1 Jombang. The design of this study is qualitative, using such instruments as interviews, observation and documentation. Data analysis in this research is reduction, display and conclusion (verification). This research result concludes that the conditions at SMAN 1 Jombang are very diverse, in terms of ethnicity, religion, social status and thinking patterns. Such tribes in the school as Java, Padang, Bugis, Sunda and Madura, then the religion includes Islam, Catholicism and Protestantism. All three are different in their belief and teaching of groups adopted. The leader of school gives freedom to all school citizen to worship and actualize based on their beliefs, so there has never been a conflict led to the diversity. This is because of the role of Islamic religion teachers and others in encouraging multicultural learning based and then resulted character tolerance can grow in the minds and actions of all school members. Keyword: Character Education, Multicultural, PAI Teachers Role